2021
DOI: 10.1021/acs.jpcb.1c05354
|View full text |Cite
|
Sign up to set email alerts
|

Femtosecond Upconversion Study of Interfacial Electron Transfer from Photoexcited CsPbBr3 Perovskite Nanocrystal to Rhodamine 6G

Abstract: Photoinduced electron transfer (PET) from an excited-state CsPbBr 3 nanocrystal (NC) to rhodamine 6G (r6G) is studied in toluene using different fluorescence-based techniques. Because of weak solubility of r6G in toluene, excess r6G molecules adsorb at NC surface which result in a much slower rotational diffusion time scale of r6G in the presence of NCs. Study of intrinsic PET benefits from the soft molecular interactions leading to donor (NC)acceptor (r6G) complex formation, where solvent diffusion parameters… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 79 publications
2
12
0
Order By: Relevance
“…FCS can record all the parameters associated with a complexation reaction, provided binding would cause PL fluctuations at a desired time scale (eq ). Association and dissociation of a quencher molecule (NMA/DNT) to the NC surface result in PL fluctuations, and the time scale of complexation reaction (τ R ) in our case was found to be slower than the average diffusion time scale (τ D ) of the NCs traversing the tiny observation volume. ,, NC + normalQ K [ NC−Q ] , goodbreak0em1em⁣ K = k + k k + and k – are the association and dissociation constants of the complexation reaction. , The binding of NC to a quencher (NMA/DNT) drops its PLQY to zero due to an efficient electron/hole transfer. Since we used mM concentration NMA/DNT, with nM concentration of NCs, the concentration of quencher (NMA/DNT) at any time during the complexation reaction is approximated to its initial concentration, i.e., [Q] ≈ [Q] 0 . Thus, the binding of NMA/DNT with NC is a pseudo-first-order reaction, and the relaxation time of the reaction dynamics (τ R ) is related to the inverse sum of k + + k – (eq ).…”
mentioning
confidence: 70%
“…FCS can record all the parameters associated with a complexation reaction, provided binding would cause PL fluctuations at a desired time scale (eq ). Association and dissociation of a quencher molecule (NMA/DNT) to the NC surface result in PL fluctuations, and the time scale of complexation reaction (τ R ) in our case was found to be slower than the average diffusion time scale (τ D ) of the NCs traversing the tiny observation volume. ,, NC + normalQ K [ NC−Q ] , goodbreak0em1em⁣ K = k + k k + and k – are the association and dissociation constants of the complexation reaction. , The binding of NC to a quencher (NMA/DNT) drops its PLQY to zero due to an efficient electron/hole transfer. Since we used mM concentration NMA/DNT, with nM concentration of NCs, the concentration of quencher (NMA/DNT) at any time during the complexation reaction is approximated to its initial concentration, i.e., [Q] ≈ [Q] 0 . Thus, the binding of NMA/DNT with NC is a pseudo-first-order reaction, and the relaxation time of the reaction dynamics (τ R ) is related to the inverse sum of k + + k – (eq ).…”
mentioning
confidence: 70%
“…2020 standard recommendation highlighting the urgency of ultrapure green (fwhm < 25 nm)-emitting materials for tv display, green LEDs, and related technologies (Table S1). , …”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the recent success of facet engineering, we have studied the HC cooling dynamics in 6-, 12-, and 26-faceted polyhedral CsPbBr 3 NCs. Interestingly, our study revealed that 12-faceted dodecahedral NCs (d-CsPbBr 3 ) and 26-faceted rhombicuboctahedral NCs (r-CsPbBr 3 ) are coveted materials characterized by polaron-mediated slower cooling (up to ∼10 times) compared to that of their cubic counterpart (c-CsPbBr 3 ) of similar size. , Subsequently, with the help of a molecular system, we successfully harvested HCs before their thermalization, signifying the tremendous implications of surface engineering for device applications. …”
mentioning
confidence: 97%